2021
DOI: 10.36076/ppj.2021/24/e357
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disc Herniation is a Nonnegligible Factor for the Degeneration of Sacroiliac Joints

Abstract: Background: Sacroiliac joint (SIJ) abnormality is a potential source of low back pain (LBP), therefore numerous patients receive various treatments because of the degenerative changes of SIJ. However, the outcome is unfavorable for patients because these morphologic alterations are common but not the origins of LBP. Previous studies revealed lumbar fusion and transitional vertebra increased the prevalence of degeneration of SIJ. Lumbar disc herniation (LDH) is one of the most common lumbar diseases, but there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…These systems also allow us to check the result of decompression intraoperatively, beyond the direct field of view in an endoscope or microscope. Retrospective studies have suggested that navigation-assisted spinal surgery can improve a patient's treatment and outcome [6,9]. However, the main disadvantages of using imaging navigation and robot assistance are the additional costs, training, and learning curve.…”
mentioning
confidence: 99%
“…These systems also allow us to check the result of decompression intraoperatively, beyond the direct field of view in an endoscope or microscope. Retrospective studies have suggested that navigation-assisted spinal surgery can improve a patient's treatment and outcome [6,9]. However, the main disadvantages of using imaging navigation and robot assistance are the additional costs, training, and learning curve.…”
mentioning
confidence: 99%